A ReaxFF molecular dynamics and RRKM ab initio based study on degradation of indene - Hashemi, S. Rasoul; Barinovs, Girts; Nyman, Gunnar (Frontiers in Astronomy and Space Sciences, 2023)
The degradation of indene is investigated using molecular dynamics (MD) with the ReaxFF force field and RRKM theory. Microcanonical rate constants are obtained over a broad energy range (8-25 eV). There is agreement between the results of the MD and RRKM calculations at the lower energies, while the MD rate constants are larger at the higher energies. At the lower energies there is also agreement with values obtained by using expressions for photodegradation of polyaromatic hydrocarbons from the literature. Those values however increase even faster with energy than our MD rate constants do. At the same time those values are lower than an experimental result at 6.4 eV. This suggests that astrochemical models employing those values may result in unreliable PAH abundances.